Oral Management of Recessive Dystrophic Epidermolysis Bullosa in Childhood: From Clinical Fragility to Functional Oral Care - Kolodziejwski, Waleska Tychanowicz; Leffa Rosa , Camila Adriane; Schussel, Juliana Lucena; de Lima , Heliton Gustavo (ARCHIVES OF HEALTH INVESTIGATION, 2025)
Introduction: Hereditary epidermolysis bullosa (EB) is a group of heterogeneous genetic disorders characterized by skin fragility, leading to blistering, erosions, and wounds on the skin and mucous membranes in response to minimal mechanical trauma with rupture at the dermoepidermal junction. Objective: To describe the oral manifestation and dental management of a patient with recessive dystrophic EB. Case report: A 6-year-old boy, diagnosed at birth with recessive EB, was referred to the dental service of the referral hospital for follow-up. Extraoral examination revealed synechiae and hand contractures, as well as blisters and crusted lesions on the upper and lower limbs. Intraoral examination showed ulcerated and erosive lesions on the lips, blisters and ulcerations on the buccal mucosa and lateral border of the tongue, tongue depapillation, petechiae on the palate, ankyloglossia, microstomia and mixed dentition with active carious lesions, gingival erythema and biofilm accumulation. Dental management included prophylaxis sessions, restorative procedures, photobiomodulation and oral hygiene instruction. Final considerations: Oral health management in EB patients requires early integration of dental care within a multidisciplinary team, adaptation of clinical techniques, use of assistive technologies, and strong emphasis on caregiver education, in order to significantly improve the quality of life for individuals living with EB.